Near-bottom current and temperature obtained from Current and Pressure-recording Inverted Echo Sounders (CPIES) and processed HYCOM data near the southwestern slope of the Chukchi Abyssal Plain ... - Ahyoung, Ku; Jae-Hun, Park (SEANOE, 2025)
Near-bottom currents and temperature were collected over a one-year period (August 2021–August 2022) using a Current- and Pressure-recording Inverted Echo Sounder (CPIES) deployed at a depth of 1060 m near the southwestern slope of the Chukchi Abyssal Plain. Similar fluctuations in currents and temperature were reproduced by the data-assimilated Hybrid Coordinate Ocean Model (HYCOM). The HYCOM output is from the GLBy0.08 Experiment 93.0, with a horizontal resolution of 0.08° × 0.04° (zonal and meridional, respectively) and a temporal resolution of 3 hours. Wind stress data, obtained from the hourly National Centers for Environmental Prediction (NCEP) Climate Forecast System Reanalysis (CFSR) and Climate Forecast System Version 2 (CFSv2), were also included. ...